The Effect of Coil Winding Replacement on the Performance of a 200 Kva Transformer (Case Study at PT. Razza Prima Trafo) - Tengku Mughayat Syah Falah; Haris Gunawan; Parlin Siagian (INFOKUM, 2025)
The electric power system is a primary need, both for daily life and for industrial life. The provision of stable and continuous electric power is an absolute requirement that must be met in meeting the need for electric power. The distribution system is the distribution of electrical energy from the substation to consumers. There are 2 (two) distribution systems, namely primary distribution and secondary distribution. Primary distribution, the distribution starts from the substation (secondary side of the power transformer) to the distribution substation (primary side of the distribution transformer) or from the substation directly to the 20kV medium voltage consumer. Power transformers are equipped with a grounding transformer that functions to obtain a neutral point from the power transformer. Before replacing the coil winding, measurements were taken using a TTR transformer turn ratio test (megger) measuring instrument. It can be concluded that the location of the damage is in the coil winding section. The results of the voltage measurements on the Primary Winding between phases R-S = 410 V, ST phase = 407 V and TR phase = 375V. and the Secondary voltage between phase and Neutral is RN = 221V, SN = 237V and TN = 222V. and the current in the Secondary winding between phases is R = 7.64A, S phase = 7.64A and T phase = 8.08A.